Bio-nanocomplexes with autonomous O2 generation efficiently inhibit triple negative breast cancer through enhanced chemo-PDT - Zhihong Zeng; Zhou Wang; Simin Chen; Chang Xiao; Minzhuo Liu; Jie Zhang; Jialong Fan; Yanzhong Zhao; Bin Liu (Journal of Nanobiotechnology, 2022)
Abstract As one kind of aggressive cancer, triple-negative breast cancer (TNBC) has become one of the major causes of women mortality worldwide. Recently, combinational chemo-PDT therapy based on nanomaterials has been adopted for the treatment of malignant tumor. However, the efficacy of PDT was partly compromised under tumor hypoxia environment due to the lack of sustainable O2 supply. In this study, CeO2-loaded nanoparticles (CeNPs) with peroxidase activity were synthesized to autonomously generate O2 by decomposing H2O2 within tumor region and reprogramming the hypoxia microenvironment as well. Meanwhile, the compound cinobufagin (CS-1) was loaded for inhibiting TNBC growth and metastasis. Moreover, the hybrid membrane camouflage was adopted to improve the biocompatibility and targeting ability of nanocomplexes. In vitro assay demonstrated that decomposition of H2O2 by CeO2 achieved sustainable O2 supply, which accordingly improved the efficacy of PDT. In turn, the generated O2 improved the cytotoxicity and anti-tumor migration effect of CS-1 by downregulating HIF-1α and MMP-9 levels. In vivo assay demonstrated that the combination of CS-1 and PDT significantly inhibited the growth and distance metastasis of tumor in MDA-MB-231 bearing mice. Thus, this chemo-PDT strategy achieved satisfactory therapeutic effects by smartly utilizing the enzyme activity of nanodrugs and special micro-environment of tumor.